A randomized, single-blind, prospective trial comparing three different gonadotropin doses with or without addition of letrozole during ovulation stimulation in patients with poor ovarian response. (August 2016) - Bastu, Ercan; Buyru, Faruk; Ozsurmeli, Mehmet; Demiral, Irem; Dogan, Murat; Yeh, John
Abstract: Objective: The aim of this randomized controlled trial (RCT) was to investigate whether IVF outcomes would differ between patients with POR who received three different gonadotropin doses with or without the addition of letrozole during ovulation stimulation. Study design: Only those who fulfilled two of the three Bologna criteria were included to the study. 95 patients met the inclusion criteria and agreed to participate in the study. In the first group, 31 patients were treated with 450 IU gonadotropins. In the second group, 31 patients were treated with 300 IU gonadotropins. The third group comprised 33 patients and was treated with 150 IU gonadotropins in combination with letrozole. Results: The results indicate that differences in doses of hMG and rFSH in patients with POR result in a similar number of retrieved MII and fertilized oocytes, similar fertilization rates, number of transferred embryos, implantation, cancelation, chemical, clinical, and ongoing pregnancy rates. Conclusions: Increasing the dose of gonadotropins during ovulation stimulation is an intuitively appealing approach when the patient is a poor responder. However, increasing the dose does not necessarily improve the reproductive outcome. Using a mild stimulation with addition of letrozole was as effective as stimulation with higher doses of gonadotropins alone in this patient population.